Implementasi Metode Analitycal Hierarchy Process (AHP) pada Sistem Pendukung Keputusan dalam Aspek Penilaian Kedisiplinan Dosen - Teguh Sri Pamungkas; Andriani Kusumaningrum (Jurnal Ilmiah SINUS, 2023)
Lecturer performance assessment is a systematic evaluation of a lecturer's work to determine each lecturer's abilities so that each lecturer can plan future career advancement for each lecturer involved. In addition, the assessment of lecturer performance is able to provide value, evaluate abilities and skills, and improve the work of a lecturer. A system has been developed for implementation of decision support systems. The purpose of this study is to help complete data processing in assessing lecturer performance so that it can help a leader choose the discipline of each lecturer. Data assessment criteria on aspects of lecturer discipline include responsibility, discipline, accuracy, expertise, attendance, personality, and communication. The method used for the lecturer assessment process is AHP (Analytic Hierarchial Process) method. Based on the results of accuracy testing on aspects of lecturer discipline with the confusion matrix testing method, the results of the Analytical Hierarchy Process (AHP) method obtained excellent accuracy values. Using the Analytical Hierarchy Process (AHP) method, an accuracy result of 80% was obtained.